PENGARUH PERSONAL BRANDING FOOD ENTHUSIAST ULFAH YUNITA PUTRI UTAMI PADA INSTAGRAM @AGAKENYANG TERHADAP MINAT KONSUMEN KULINER - RESZYNIA YULIARTI (Jurnal Visi Komunikasi, 2020)
Personal brands are built so that other people have a positive outlook so that they can continue to trust or to other actions. A strong personal brand always has three basic things that stick together, as has been written by McNally & Speak (2004), namely uniqueness, relevance and consistency. This study uses a positivism paradigm with explanatory research type and survey research methods. In conducting research on Instagram @agakenyang, the author created a questionnaire which was then distributed to @agakenyang Instagram followers. In this study, it was found that (i) the dimensions of specificity with the dimensions of transactional interest, preferential interest and explorative interest have a moderate level of relationship between the values of 0.40 - 0.599, (ii) the dimension of relevance to the dimensions of exploratory interest has a strong level of relationship, namely with value of 0.625, (iii) the dimension of consistency with the dimension of transactional interest has a strong level of relationship, namely with a value of 0.601 and (iv) the effect of Personal Branding on Culinary Consumer interest is 53.29%.